Emergency Radiology III - Chest and Limb Trauma. Issue 4 (1st December 2012) - Archer, J; Russell, Rob; Perry, J
Abstract : This is the final of three self-assessment articles which aims to further readers' understanding of diagnostic imaging, and its integral role in the management of patients with emergency conditions, through a series of case studies.